Penerapan Strategi Menyanyi dalam Pembelajaran Kosa Kata Bahasa Arab di SD Muhammadiyah - Attamimi, Helfi Ahsan; Fauji, Imam (Jurnal Naskhi Jurnal Kajian Pendidikan dan Bahasa Arab, 2025)
Learning Arabic vocabulary is a challenge for students, especially in creating a fun and effective atmosphere. This research discusses the application of singing strategies in learning Arabic vocabulary at SD Muhammadiyah 1 Sedati. The method used is descriptive qualitative research with data collection techniques through interviews, observation and documentation. The research results show that the singing strategy is implemented through three main stages, namely planning, implementation and evaluation. In practice, the use of songs with lyrics adapted to the material helps students more easily memorize number vocabulary in Arabic. However, problems were found in the writing aspect, where most students still had difficulty writing down the vocabulary they had memorized. Supporting factors in this learning include the availability of textbooks, a conducive learning environment, and the role of competent teachers. Meanwhile, inhibiting factors include lack of use of technology and minimal writing practice. The solution offered is to combine singing strategies with writing practice and increase the use of technology in learning. Thus, the singing strategy has proven to be effective in increasing students' understanding and interest in learning Arabic vocabulary, although it still needs to be combined with other methods for more optimal results.Keywords: Singing strategies, vocabulary learning, Arabic, active methods, Muhammadiyah Elementary School